Self‐Adhesive Silicone Microstructures for the Treatment of Tympanic Membrane Perforations. Issue 10 (8th October 2021) - Moreira Lana, Gabriela; Sorg, Katharina; Wenzel, Gentiana Ioana; Hecker, Dietmar; Hensel, René; Schick, Bernhard; Kruttwig, Klaus; Arzt, Eduard
Abstract : Bioinspired Adhesives Novel material architectures for accelerated healing ‐ silicone microstructures are proposed as bioinspired non‐chemical adhesive for repairing tympanic membranes. The novel patch adapts and adheres to the injured eardrum and supports scarless healing. Handling by the surgeon is improved and allows for a new paradigm in out‐patient treatment. More details can be found in article number 2100057 by Eduard Arzt and co‐workers.